2021
DOI: 10.1002/aic.17272
|View full text |Cite|
|
Sign up to set email alerts
|

Micromembrane absorber with deep‐permeation nanostructure assembled by flowing synthesis

Abstract: A micromembrane adsorber with deep‐permeation nanostructure (DPNS) has been successfully fabricated by flowing synthesis. The nanoparticles are in‐situ assembled in membrane pores and immobilized in each membrane pore along the direction of membrane thickness. The nanoparticles with a lower size and thinner size distribution can be achieved owing to the confined space effect of the membrane pores. As a concept‐of‐proof, the nano ZIF‐8 and ZIF‐67 are fabricated in porous membrane pores for methyl orange (MO) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In our previous study, it has been found that the catalytic nanoparticles can be in situ immobilized in membrane pores by flowing synthesis [16][17][18][19][20] . During this process, the precursor fluid for nanoparticles formation can permeate through the membrane pores under the external driven force.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, it has been found that the catalytic nanoparticles can be in situ immobilized in membrane pores by flowing synthesis [16][17][18][19][20] . During this process, the precursor fluid for nanoparticles formation can permeate through the membrane pores under the external driven force.…”
Section: Introductionmentioning
confidence: 99%
“…Flowing synthesis is an effective method to immobilize a nanoatalyst into the pores of a porous substrate. Instead of by diffusion of the precursor liquid into the porous substrate pores under the condition of a porous substrate immersed into a precursor liquid, the precursor liquid can flow into the pores by the action of external force under the condition of flowing synthesis. In this case, each pore of the porous substrate can be filled with the precursor liquid, and the nanocatalyst can be firmly immobilized in the pores of the porous substrate due to the van der Waals force and inertia force.…”
Section: Introductionmentioning
confidence: 99%
“…However, traditional polymeric membranes used in the energy related techniques have to suffer from an insurmountable paradox between ion selectivity and conductivity, usually called the trade‐off effect 6 . To alleviate this limitation, porous membranes whose nanopores act as the sieving role exhibit grand potential as ion selective membranes 7–9 . Up to now, various studies on porous membranes, including membrane microstructure design, 10,11 membrane property modification 12,13 and membrane material synthesis, 14 have been carried out, particularly for the vanadium flow battery (VFB) system.…”
Section: Introductionmentioning
confidence: 99%
“…6 To alleviate this limitation, porous membranes whose nanopores act as the sieving role exhibit grand potential as ion selective membranes. [7][8][9] Up to now, various studies on porous membranes, including membrane microstructure design, 10,11 membrane property modification 12,13 and membrane material synthesis, 14 have been carried out, particularly for the vanadium flow battery (VFB) system. Notably, porous membranes consisted of molecular sieving materials such as zeolites and metal-organic frameworks (MOFs) present intrinsic merits compared with porous polymeric membranes, involving regular pore structure and modifiable channels.…”
Section: Introductionmentioning
confidence: 99%